Ayurvedic Management of Infertility W.S.R. to Tubal Blockage by Kshar Taila Uttar Basti: A Case Study - Preeti Chouhan; Ayush Kumar Garg (Wolters Kluwer Medknow Publications, 2024)
Introduction: Fallopian tube blockage is an important factor for female infertility. Fallopian tubes can be correlated with the Artavavaha Srotas and the block is compared with the Sanga Srotodushti (obstruction in channels). This article discusses a 28-year-old female patient with a history of 10 years of infertility. Main Clinical Finding: In this case study, the patient was anxious to conceive after 10 years of a regular and satisfactory marital relationship. Diagnosis: The patient was diagnosed with primary infertility due to bilateral tubal blockage after allopathic consultation and was advised for in vitro fertilization. However, she was indisposed to do so because of her low socioeconomic condition. Hence, she approached the Outpatient Department of Prasuti Tantra, Sir Sunderlal Hospital, IMS, BHU. Interventions: After appropriate analysis based on Ayurvedic and modern parameters, the patient was treated with Kshar Taila Uttar Basti (UB) along with oral medications. The management was to remove the blockage in the fallopian tubes. Outcome: Two cycles of treatment were given and the patient came with positive urine pregnancy test with the complaint of 2-month amenorrhea. Then, she took regular antenatal care and delivered a baby boy after 9 months of pregnancy through cesarean delivery (C-section). Conclusions: Hence, here, management with Kshar Taila UB has been proved to be a very effective treatment modality to treat tubal blockage.